2020
DOI: 10.3389/fgene.2020.00091
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of DNA Methylation and Long Non-Coding RNA Expression in Gastric Cancer

Abstract: Abnormal DNA methylation, an epigenetic modification, has increasingly been linked to the pathogenesis of many human cancers. However, there has been little focus on the DNA methylation patterns of genes encoding long noncoding RNAs (lncRNAs) in gastric cancer (GC). This study comprehensively determined DNA methylation and lncRNA expression profiles in GC through genome-wide analysis. Differentially methylated loci and lncRNAs were identified by integrating multi-omics data. In total, 548 differentially methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…10 -20 % methylation). This was consistent with findings from past literature where biomarkers with a difference in mean methylation of 10 -20 % was considered as "significant" biomarkers with potential for future testing [18], [19], [22], [30].…”
Section: Comparison Of Parametric and Non-parametric Testingsupporting
confidence: 91%
“…10 -20 % methylation). This was consistent with findings from past literature where biomarkers with a difference in mean methylation of 10 -20 % was considered as "significant" biomarkers with potential for future testing [18], [19], [22], [30].…”
Section: Comparison Of Parametric and Non-parametric Testingsupporting
confidence: 91%
“…As is known, abnormal DNA methylation is related to many cancers, and this epigenetic disruption may lead to abnormal lncRNA expression in tumor tissues [20]. Evidence has shown that lncRNAs generated in HOX family genes, as HOTAIR, HOTTIP, HOXA11-AS, HOXB-AS4, and HOXC-AS3, were regulated by aberrant DNA methylation in GC [21]. However, the roles and mechanism of lncRNA HOXB-AS4 in GC remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating and reanalyzing the RNA-seq or microarray data using bioinformatics methods may help identify gene regulatory pathways, essential genes, and their associated networks in different diseases, providing information on the possible molecular mechanisms of diseases, potential drug research, and development directions [ 20 , 21 ]. Some studies have precisely revealed details on tumor microenvironment crosstalk [ 22 , 23 ] and the effect of epigenetic modification on tumor development [ 24 ]. In this study, we found that some cytokines, especially CXCL1, showed a significant difference in expression after treatment with belinostat.…”
Section: Introductionmentioning
confidence: 99%